Publisher Correction: Imaging the square of the correlated two-electron wave function of a hydrogen molecule - M. Waitz (Nature Portfolio, 2018)
The original version of this Article contained an error in the fifth sentence of the first paragraph of the ‘Application on H2’ section of the Results, which incorrectly read ‘The role of electron correlation is quite apparent in this presentation: Fig. 1a is empty for the uncorrelated Hartree–Fock wave function, since projection of the latter wave function onto the 2pσ u orbital is exactly zero, while this is not the case for the fully correlated wave function (Fig. 1d); also, Fig. 1b, c for the uncorrelated description are identical, while Fig. 1e, f for the correlated case are significantly different.’ The correct version replaces ‘Fig. 1e, f’ with ‘Fig. 2e and f’.